বীজগণিতের যাবতীয় সুত্রাবলি (a + b) 2 = a 2 + 2ab + b 2 (a + b) 2 = (a – b) 2 + 4ab (a – b) 2 = a 2 – 2ab + b 2 (a – b) 2 = (a + b) 2 – 4ab a 2 + b 2 = (a + b) 2 – 2ab a 2 + b 2 = (a – b) 2 + 2ab a 2 – b 2 = (a + b) – (a – b) 2 (a 2 + b 2 ) = (a + b) 2 + (a – b) 2 (a + b + c) 2 = (a 2 + b 2 + c 2 ) + 2 (ab + bc + ca) (a 2 + b 2 + c 2 ) = (a + b + c) 2 – 2(ab + bc + ca) 2 (ab + bc + ca) = (a + b + c) 2 – (a 2 + b 2 + c 2 ) (a + b) 3 = a 3 + 3a 2 b + 3ab 2 + b 3 (a + b) 3 = a 3 + b 3 + 3ab (a + b) (a – b) 3 = a 3 – 3a 2 b + 3ab 2 – b 3 (a – b) 3 = a 3 – b 3 – 3ab (a – b) a 3 + b 3 = (a + b) ( a 2 – ab + b 2 ) a 3 + b 3 = (a + b) 3 – 3ab (a +...